Bimetallic gold nanorods with enhanced biocorona formation for doxorubicin loading and sustained release. (4th December 2018) - Chakraborty, Debolina; Mohan, Lavanya; Alex, Sruthi Ann; Chandrasekaran, Natarajan; Mukherjee, Amitava
Abstract : Bimetallic coating over gold nanorods improves biocorona formation, enhances drug loading and release, and reduces non-specific in vitro toxicity. Abstract : The biomedical applicability of gold nanorods (AuNRs) arises due to their interesting optical and photothermal properties, which can result in the formation of a protein corona layer when exposed to the physiological system. The current study focuses on the effect of bimetallic coatings of AuNRs (AuNRs@Pd and AuNRs@Cu) on protein corona formation, and the potential application of protein-coronated bimetallic AuNRs was investigated for doxorubicin (dox) loading, release, and in vitro cytotoxicity analysis. Two significant proteins in blood serum, namely, human serum albumin (HSA) and transferrin, were chosen for the protein coronation. The variations in the protein adsorption patterns of monometallic and bimetallic AuNRs were studied based on the protein adsorption, zeta potential, and particle size measurements. A higher adsorption of hard and soft corona was observed for HSA due to their higher abundance and reactivity. The enhanced electropositive nature of these bimetals promoted higher corona formation (AuNR@Pd > AuNR@Cu > AuNRs) when compared with bare AuNRs, which in turn correlated with higher dox loading. The higher corona on bimetallic AuNRs helped to overcome the burst release of dox over a period of 48 h (AuNRs@Pd > AuNR@Cu > AuNRs) when compared to the respective monometallic AuNRs, and the dox release was slightly increased when tested in human plasma. Furthermore, a significant decrease in the cytotoxicity of protein-coronated bimetallic AuNRs as compared to monometallic AuNRs was also observed. Thus, it can be suggested that the use of engineered protein corona on bimetallic nanostructures can open new areas of research for cancer therapeutics.